2022
DOI: 10.1186/s12934-022-01819-z
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization and transporter engineering strategies for terpenoid synthesis

Abstract: Microbial cell factories for terpenoid synthesis form a less expensive and more environment-friendly approach than chemical synthesis and extraction, and are thus being regarded as mainstream research recently. Organelle compartmentalization for terpenoid synthesis has received much attention from researchers owing to the diverse physiochemical characteristics of organelles. In this review, we first systematically summarized various compartmentalization strategies utilized in terpenoid production, mainly plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 125 publications
0
20
0
Order By: Relevance
“…To circumvent nonproductive consumption of intermediates and reduce cell toxicity caused by excessive metabolites, compartmentalizing is usually a good solution for heterologous biosynthesis. , The peroxisome is considered to have a high content of the acetyl-CoA pool from the β-oxidation of fatty acids, rendering it more propitious for MVA pathway compartmentalization . Here, the enhanced peroxisome targeting sequence (ePTS1) was employed to target enzymes of the trans -nerolidol biosynthetic pathway into the peroxisome.…”
Section: Resultsmentioning
confidence: 99%
“…To circumvent nonproductive consumption of intermediates and reduce cell toxicity caused by excessive metabolites, compartmentalizing is usually a good solution for heterologous biosynthesis. , The peroxisome is considered to have a high content of the acetyl-CoA pool from the β-oxidation of fatty acids, rendering it more propitious for MVA pathway compartmentalization . Here, the enhanced peroxisome targeting sequence (ePTS1) was employed to target enzymes of the trans -nerolidol biosynthetic pathway into the peroxisome.…”
Section: Resultsmentioning
confidence: 99%
“…The solution is to implement compartmentalization, omnipresent in existing living organisms (de Lorenzo et al, 2015; Quinlivan et al, 2003). From this perspective, organelle compartmentalization for terpenoid synthesis has been the subject of much research attention, due to the diversity of the original physico‐chemical characteristics of organelles (Jin et al, 2022). A rather different, but certainly effective, way of compartmentalizing metabolic reactions is to set up co‐cultures involving different organisms that develop sub‐pathways assembled together via their import and export of intermediates.…”
Section: Sustainability‐driven Metabolic Engineeringmentioning
confidence: 99%
“…Frontiers in Bioengineering and Biotechnology frontiersin.org Yocum et al, 2021;Jin et al, 2022), as shown in Table 1. The physiological properties of various organelles as well as their benefits and drawbacks for organelle compartmentalization in terpenoid production (Jin et al, 2022), which will not be discussed below.…”
Section: Introductionmentioning
confidence: 99%
“…Frontiers in Bioengineering and Biotechnology frontiersin.org Yocum et al, 2021;Jin et al, 2022), as shown in Table 1. The physiological properties of various organelles as well as their benefits and drawbacks for organelle compartmentalization in terpenoid production (Jin et al, 2022), which will not be discussed below. In this review, we summarize the characteristics of monoterpenoids, sesquiterpenoids and tetraterpenoids and focuse on their unique requirements for improving terpenoid production through organelle compartmentalization.…”
Section: Introductionmentioning
confidence: 99%